Impacto de la maternidad en el aprendizaje de las estudiantes Universitarias - Zula Riofrío, Paul David (2024)
Motherhood is made up of social and historical discourses and practices, which are imaginary, complex and powerful, which are associated with gender. Historically, women have been assigned care functions, in addition to academic responsibilities. This work aims to show some results achieved from the execution of a research project. The objectives of the project are: to analyze the impact of motherhood on the learning of university students; and, as specific objectives, to identify the sociodemographic conditions of students in maternity situations; determine the sociodemographic factors that are related to the learning of students in maternity situations; and; design a methodological guide that facilitates the learning process in university mothers of the Faculty of Human Health of the National University of Loja, through a quantitative, explanatory, cross-sectional study. The methodological process was carried out by applying a survey, focused on the sociodemographic conditions and learning conditions of the students who are mothers, which allowed the analysis of the results. Sociodemographic conditions such as marital status: 40% are single, 85% receive support from their family, and 44% receive help from their parents, providing support for them to continue studying. Regarding support from teachers during maternity, 8% have their help; Likewise, it is determined that 61% of the students have thought about withdrawing from their degree at some point. 66% mention that motherhood affects academic performance. In this way, it can be concluded that motherhood affects their learning, which demonstrates that the balance between maternal responsibilities and educational commitments entails practical and emotional difficulties, including absenteeism, poor academic performance, and the possibility of dropping out of school. Keywords: Academic performance, mothers, motherhood, professional education.